STRATEGIES DE SURVIE DES MEMBRES DU PERSONNEL SCIENTIFIQUE NON MECANISES DE L’UNIVERSITE DE KISANGANI - Lucien MUSAMBAY RAMAZANI; Gloria, Ruphin Zongodio (IJRDO - Journal of Social Science and Humanities Research, 2022)
Nowadays in Democratic Republic of Congo, the sector of higher Education and University faces serious problems wich fragilize its good function. However, the public university et higher institutes get the services from population and so from their agents. This sector of national life should contribute thoughly to the development of members of scientific personnel of Kisangani University. After making this study on « the strategies of survive of members of scientific personnel non payed of Kisangani University », it is better to decode several mechanisms used by scientific personnel non payed in order to link the two ends of months.